Spinocerebellar Ataxia 3 (SCA3) Patient with Peripheral Neuropathy - Siti Aminah Sobana; Iin Pusparini; Nushrotul Lailiyya; Ahmad Rizal Ganiem; Uni Gamayani; Yusuf Wibisono; Fathul Huda; Yunia Sribudiani; Tri Hanggono Achmad (Faculty of Medicine, Universitas Padjadjaran, 2022)
Spinocerebellar ataxia (SCA) 3 is a neurodegenerative disease which involves cerebellum and extra cerebellum. Neuropathy in SCA3 manifests in various ways, including axonal and demyelination lesions in sensory and motor nerves. There has not been any study that describes the peripheral neuropathy characteristics of SCA3 patients in Indonesia at the time of this publication. This paper reports a case of a 43-year-old male with known spinocerebellar ataxia 3 presented with hereditary ataxia and mild numbness in both palms since two years before. No abnormalities were found during the sensory examination. The NCS showed severe axonal demyelinating sensorimotor peripheral neuropathy. In magnetic resonance imaging (MRI), an atrophy in the cerebellum with cerebral multiple lacunar infarction was identified. Electrophysiological results revealed profound axonal lesion in peripheral nerves. To conclude, peripheral neuropathy in SCA3 represents the dominance of axonal lesions in motor nerves.